Diagnosis and Risk Factors of Acute Kidney Injury in Very Low Birth Weight Infants - Ankana Daga; Fredrick Dapaah-Siakwan; Sharina Rajbhandari; Cassandra Arevalo; Agnes Salvador (Pediatrics and Neonatology)
Acute kidney injury (AKI) is common in critically ill premature infants. There is a lack of consensus on the diagnostic definition of AKI in very low birth weight (VLBW) infants. The primary aim of this study was to determine the incidence and risk factors for AKI in VLBW infants using the AKI network (AKIN) and pRIFLE (pediatric Risk, Injury, Failure, Loss, End-Stage) criteria and to evaluate whether Clinical Risk Index for Babies (CRIB II) score is a predictor of AKI. The secondary objective was to determine the extent of agreement between the AKIN and pRIFLE criteria in the diagnosis of AKI in VLBW infants. Methods: This was a retrospective chart review of 115 VLBW (< 1500 g) infants born in an academic center with a Level 3B neonatal intensive care unit. Multiple congenital anomalies, transfer to other centers, or death within the first 2 weeks were the exclusion criteria. Relevant data were collected and analyzed in the first 2 weeks postnatally. Results: AKI incidence, according to AKIN and pRIFLE criteria, was 20.1% and 22.6%, respectively. As per the interrater reliability analysis, there was a fair agreement between the two criteria (kappa = 0.217). AKI was nonoliguric. The length of stay was significantly longer in the AKI group. Prenatal nonsteroidal anti-inflammatory drug exposure, lower gestational age, lower birth weight, respiratory distress syndrome, mechanical ventilation, patent ductus arteriosus, hypotension, late onset sepsis, and higher CRIB II scores were significantly associated with AKI. Our regression analysis found CRIB II scores to be an independent risk factor for AKI (odds ratio = 1.621; 95% confidence interval, 1.230–2.167; p = 0.001). Conclusion: The determination of AKI using the pRIFLE and AKIN criteria yielded different results. pRIFLE appears to be more sensitive in VLBW infants. A high CRIB II score was recorded for AKI. Future studies are necessary to develop a uniform definition and identify the risk factors to improve the outcomes in this population.